2009
DOI: 10.3109/03091900903067440
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the antero-posterior and rotational stability of the anterior cruciate ligament analogue in a guided motion bi-cruciate stabilized total knee arthroplasty

Abstract: Abnormal knee kinematics and sagittal instability after most knee replacements are due in part to deficient anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) function. The guided motion bi-cruciate stabilized knee replacement aspires to stabilize the knee posteriorly and anteriorly by means of a cam-post mechanism. This investigation studies the ACL-stabilizing function of that mechanism in early flexion, and 25 knees that had undergone replacement with this implant were studied. Antero-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The goal is to provide a “guided motion” which should lead to kinematics similar to that of a normal knee [ 16 – 19 ]. This guided motion has been reported in different studies comparing the JOURNEY™ I BCS prosthesis to other TKA systems and normal knees [ 20 25 ]. In vivo fluoroscopic studies demonstrated that nearly normal kinematic motions can be attained with the JOURNEY™ BCS TKS [ 21 , 22 , 24 , 26 30 ].…”
Section: Introductionsupporting
confidence: 61%
“…The goal is to provide a “guided motion” which should lead to kinematics similar to that of a normal knee [ 16 – 19 ]. This guided motion has been reported in different studies comparing the JOURNEY™ I BCS prosthesis to other TKA systems and normal knees [ 20 25 ]. In vivo fluoroscopic studies demonstrated that nearly normal kinematic motions can be attained with the JOURNEY™ BCS TKS [ 21 , 22 , 24 , 26 30 ].…”
Section: Introductionsupporting
confidence: 61%
“…More lasting feelings of instability are recorded as lower functional outcome scores on such questionnaires and could occur during every execution of a task. Anterior/posterior (A/P) laxity as determined by a Lachman test (either manual or instrumented with a KT-2000 arthrometer or Rolimeter) varies considerably between different groups of TKA patients, [22][23][24][25] and the use of fluoroscopy has shown paradoxical sliding motions in some activity phases between the femur and the tibia of TKA patients. 26,27 However, research on ACL-deficient knees has shown that passive knee laxity characterized by these tests is not related to knee stability during dynamic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Different concepts (kinematic alignment) and designs (BCSKS/medial pivot knee/bicruciate retaining knee) are evolving to overcome this problem. First-generation dual cam BCSKS was introduced in 2005 to reproduce normal kinematics and accounts for the lack of ACL by creating anterior cam and post [ 6 ]. This is unique from the posterior stabilized knee arthroplasty designs in many aspects (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%